2005
DOI: 10.1523/jneurosci.3813-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen for Mutations That Affect Cranial Nerve Development in the Mouse

Abstract: Cranial motor and sensory nerves arise stereotypically in the embryonic hindbrain, act as sensitive indicators of general and regionspecific neuronal development, and are directly or indirectly affected in many human disorders, particularly craniofacial syndromes. The molecular genetic hierarchies that regulate cranial nerve development are mostly unknown. Here, we describe the first mouse genetic screen that has used direct immunohistochemical visualization methods to systematically identify genetic loci requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
1
18
0
Order By: Relevance
“…A genetic screen for cranial nerve mutations in mouse indicated that Pax3 is required for growth of the facial nerve, as well as formation of the lower jaw (Mar et al, 2005). While these Pax3 phenotypes resemble some of the OM2 phenotypes in our current studies, it is clear that the OM2 phenotypes suggest a more complex regulation of branchiomotor axon growth than has been described for Pax3 in mouse.…”
Section: 2supporting
confidence: 50%
“…A genetic screen for cranial nerve mutations in mouse indicated that Pax3 is required for growth of the facial nerve, as well as formation of the lower jaw (Mar et al, 2005). While these Pax3 phenotypes resemble some of the OM2 phenotypes in our current studies, it is clear that the OM2 phenotypes suggest a more complex regulation of branchiomotor axon growth than has been described for Pax3 in mouse.…”
Section: 2supporting
confidence: 50%
“…Another reporter screen assaying axon guidance recovered 7 mutants from 57 lines (12%) with 6 affecting the reporter allele expression (Dwyer et al 2011). A immunohistochemical approach to studying cranial nerve development yielded seven mutants from 40 pedigrees [18% (Mar et al 2005)]. …”
Section: Discussionmentioning
confidence: 99%
“…To identify novel factors essential for the development of the peripheral nervous system (PNS), we have developed a three-generation, forward genetic screen for recessive mutations affecting the patterning and guidance of PNS axonal projections (Mar et al, 2005). First, 8- to 10-week-old, male, C57BL/6 (BL6) mice (F1) were intraperitoneally injected with 300mg of ENU to randomly induce point mutations throughout the mouse genome.…”
Section: Resultsmentioning
confidence: 99%